Estimation of Salivary Candida Count Among Pregnant and Non-Pregnant Women - Fareeha Aleem, Tehmina Munir, Afia Shafiq, Farhat Abbas Bhatti, Syeda Fatima Babar, Faizan Hamid (Journal of Islamic International Medical College, 2024)
Objective: Comparison of Candida count in the saliva of pregnant and non-pregnant women to determine how much salivary Candida count increases in pregnancy as compared to non-pregnant women. Study Design: Cross-sectional study. Place and Duration of Study: Pathology Dental Department, HITEC-IMS Hospital Taxila Cantt from 2 December 2021-30 May 2022. Materials and Methods: The study included 60 pregnant and 60 non-pregnant women of age group ranging from 18 to 40 years. The unstimulated whole saliva of the subjects was collected in sterile plastic containers. The sample was inoculated on Sabouraud dextrose agar. The grown colonies were counted after 48 to 72 hours. Gram staining was performed to confirm the presence of Gram-positive oval budding Candida. Results: The Candida count from the saliva of pregnant women was two times greater in number than saliva of non-pregnant women. The mean value in pregnant women was 237.7 CFU/ml while in non-pregnant, it was 103 CFU/ml. Conclusion: The changes during pregnancy make the oral cavity of pregnant women more vulnerable leading to increased growth of Candida and that increase is twice more than that of non-pregnant women